The Development of Horizontal Anchor Items Test Tool by Rasch Model for Physics National Examination using Macromedia Flash - Yetti Supriyati; Raihanati Raihanati; Wirda Nilawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
This study aims to develop a Macromedia Flash-based test device using Horizontal Anchor Items for the National Examination in High School Physics lessons. The research method used in this study is research and development. This research and development uses a qualitative and quantitative approach and uses the Research and Development (R & D) development model of the Dick and Carey model. The results of the validation test of the National Examination test instrument by material experts showed that the National Examination test instrument that had been developed had very good quality (91.25%) when viewed in terms of material. Besides, the results of the validation test of the National Examination test instrument by media experts showed that the National Examination test instruments that had been developed had very good quality (87.5%) when viewed in terms of media. In the first stage of the empirical test, the first reliability test device was quite good, while the second test device showed sufficient reliability. Besides that, the two test kits showed that all items were declared valid. The results of the Person fit for the test respondent of the first test device, and the second test device showed that there were no respondents who were inconsistent, careless, lucky, or cheating. In the second stage of the empirical test, the first test device showed quite good reliability, while the second test device showed sufficient reliability. Besides that, both the test kits show that all items are declared valid. The results of the Person fit for the test respondent of the first test device, and the second test device showed that there were no respondents who were inconsistent, careless, lucky, or cheating. In the third empirical test, the first test device showed good reliability, while the test device showed sufficient reliability. Besides that, the two test kits showed that all items were declared valid. The results of the Person fit for the test respondent of the first test device, and the second test device showed that there were no respondents who were inconsistent, careless, lucky, or cheating. So that the two test kits were declared feasible and could be used for the implementation of the Computer-Based National Examination in Physics.